MICROSTRUCTURE OF HDTMA+-MODIFIED MONTMORILLONITE AND ITS INFLUENCE ON SORPTION CHARACTERISTICS - He H.; Zhou Q.; Martens W.N.; Kloprogge T.J.; Yuan P.; Xi Yu.; Zhu J.; Frost R.L. (My University, 2006)
A series of organoclays with monolayers, bilayers, pseudotrilayers, paraffin monolayers and paraffin bilayers were prepared from montmorillonite by ion exchange with hexadecyltrimethylammonium bromide (HDTMAB). The HDTMAB concentrations used for preparing the organoclays were 0.5, 0.7, 1.0, 1.5, 2.0 and 2.5 times the montmorillonite cation exchange capacity (CEC). The microstructural parameters, including the BET-N2 surface area, pore volume, pore size, and surfactant loading and distribution, were determined by X-ray diffraction, N2 adsorption-desorption and high-resolution thermogravimetric analysis (HRTG). The BET-N2 surface area decreased from 55 to 1 m2/g and the pore volume decreased from 0.11 to 0.01 cm3/g as surfactant loading was increased from Na-Mt to 2.5CEC-Mt. The average pore diameter increased from 6.8 to 16.3 nm as surfactant loading was increased. After modifying montmorillonite with HDTMAB, two basic organoclay models were proposed on the basis of HRTG results: (1) the surfactant mainly occupied the clay interlayer space (0.5CEC-Mt, 0.7CEC-Mt, 1.0CEC-Mt); and (2) both the clay interlayer space and external surface (1.5CEC-Mt, 2.0CEC-Mt, 2.5CEC-Mt) were modified by surfactant. In model 1, the sorption mechanism of p-nitrophenol to the organoclay at a relatively low concentration involved both surface adsorption and partitioning, whereas, in model 2 it mainly involved only partitioning. This study demonstrates that the distribution of adsorbed surfactant and the arrangement of adsorbed HDTMA+ within the clay interlayer space control the efficiency and mechanism of sorption by the organoclay rather than BET-N2 surface area, pore volume, and pore diameter.
Keywords: BET-N2 SURFACE AREA; HDTMA+; ORGANOCLAY; PORE SIZE; PORE VOLUME; SORPTION EFFICIENCY; SURFACTANT LOADING; SORPTION MECHANISM